Prevalence of dyslipidaemia in type 2 diabetes mellitus patients and its association to diabetic retinopathy in a Malaysian tertiary hospital - Samsudin, Intan Nureslyna; Md Saleh, Rafidah; Chellappah Thambiah, Subashini; Mohamad Amir Hamzah, Aiffa Syafira; Wan Khalik, Wan Noor Fatini; George, Elizabeth (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Background: Diabetic retinopathy (DR) is a microvascular complication of diabetes, which is a cause of visual impairment and blindness. Its development and progression have been linked to dyslipidaemia, although the link remains inconclusive. Aim: This study aimed to determine the prevalence of dyslipidaemia among type 2 diabetic patients with DR in a tertiary setting and to determine the association between dyslipidaemia and DR severity. Materials and methods: This was a cross sectional study using retrospective data of type 2 diabetic patients attending the opthalmology clinic of a tertiary centre from January 2007 to June 2014. Results of their fasting lipid profile and clinical data were retrieved from the hospital information system. Results: A total of 178 patient’s data were collected. 120 (n=67.4%) patients had non-proliferative diabetic retinopathy (NDPR) with moderate NPDR being the most prevalent. Dyslipidaemia was noted in 151 (84.8%) of the patients. Patients had a combination of more than one abnormality in the lipid profile with increased LDL-cholesterol being the main abnormality. Dyslipidaemia was however, not significantly associated with DR severity. Conclusion: Dyslipidaemia was highly prevalent in DR patients. The dyslipidaemia was however not associated with severity of DR.